2019
DOI: 10.1002/cm.21516
|View full text |Cite
|
Sign up to set email alerts
|

Using the SpyTag SpyCatcher system to label smooth muscle myosin II filaments with a quantum dot on the regulatory light chain

Abstract: The regulatory light chain (RLC) of myosin is commonly tagged to monitor myosin behavior in vitro, in muscle fibers, and in cells. The goal of this study was to prepare smooth muscle myosin (SMM) filaments containing a single head labeled with a quantum dot (QD) on the RLC. We show that when the RLC is coupled to a QD at Cys‐108 and exchanged into SMM, subsequent filament assembly is severely disrupted. To address this, we used a novel approach for myosin by implementing the SpyTag002 SpyCatcher002 system to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A spontaneous covalent isopeptide bond forms between a lysine residue of the SpyCatcher domain (13 kDa) and an aspartic acid of its pairing peptide SpyTag (13 amino acid residues) in a sitespecific manner, without the need of additional reagents nor enzymes at broad ligation conditions (Reddington and Howarth, 2015). The advantageous properties of the SpyTag/SpyCatcher chemistry makes it an excellent protein ligation tool for surface functionalization of various organic and inorganic materials, such as virus-like particles (Brune et al, 2016(Brune et al, , 2017Bruun et al, 2018), protein-based scaffolds (Bae et al, 2018;Choi et al, 2018;Swartz and Chen, 2018;Zhang et al, 2018a), gold nanoparticles (Ma et al, 2018), silica (Zhang et al, 2018b,c), quantum dots (Ke et al, 2018;Brizendine et al, 2019), and crystalline graphene (Tyagi et al, 2018). We recently developed a modular PHA platform using SpyTag/SpyCatcher chemistry, where we successfully showed that purified SpyTagged proteins could ligate to SpyCatcher-coated PHA spheres in vitro with decent tunability (Wong and Rehm, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A spontaneous covalent isopeptide bond forms between a lysine residue of the SpyCatcher domain (13 kDa) and an aspartic acid of its pairing peptide SpyTag (13 amino acid residues) in a sitespecific manner, without the need of additional reagents nor enzymes at broad ligation conditions (Reddington and Howarth, 2015). The advantageous properties of the SpyTag/SpyCatcher chemistry makes it an excellent protein ligation tool for surface functionalization of various organic and inorganic materials, such as virus-like particles (Brune et al, 2016(Brune et al, , 2017Bruun et al, 2018), protein-based scaffolds (Bae et al, 2018;Choi et al, 2018;Swartz and Chen, 2018;Zhang et al, 2018a), gold nanoparticles (Ma et al, 2018), silica (Zhang et al, 2018b,c), quantum dots (Ke et al, 2018;Brizendine et al, 2019), and crystalline graphene (Tyagi et al, 2018). We recently developed a modular PHA platform using SpyTag/SpyCatcher chemistry, where we successfully showed that purified SpyTagged proteins could ligate to SpyCatcher-coated PHA spheres in vitro with decent tunability (Wong and Rehm, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Chicken smooth muscle RLC (UniProtKB-P02612) and SpyTag002 (RLC-Spy) construct was expressed and purified as described ( Brizendine et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Modification of QDs was performed similar to that described in Brizendine et al (2019) . Briefly, amine QDs (Invitrogen; 50 µl of 605 or 705 nm; 8 µM) were centrifuged for 3 min at 2,400× g and washed twice in a 100 kD cutoff centrifugal filter unit (Millipore) in DTT-free conjugation buffer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations